CURRENT MEDICAL CONTROL OF FOOTBALL REFEREES DURING EDUCATIONAL TRAINING CAMP (SPECIALLY-PREPARATORY PHASE) - T.O. Tereshchenko; N.M. Nazarko (Bogomolets National Medical University, 2016)
Physical training is the important part of general training of football referees. Specially-preparatory phase is more similar to the actions of the referee during the match and characterizes a decrease of the duration of exercise with increasing intensity. Hard on the volume and intensity physical activity suffered by referees during matches and training can not only lead to overtraining or decline the level of special physical fitness, but also contribute to pathological changes in the body of the referees. Therefore, an important part of evaluating of readiness of football referees to physical training is the current medical monitoring, which individualizes training process. We analyzed the peculiarities of adaptation of the football referees to physical activities to optimize current medical control. We examined 70 high qualifications football referees and assistants referee aged 35.33±0.55 years by means of anamnestic, anthropometric, tonometric and pulsometric methods with followed calculation of indices (body mass index, mean dynamic arterial pressure, pulse pressure, Robinson index, coefficient of blood circulation efficiency, stamina coefficient, adaptive capacity, index Kerdo). The results show that the integrated hemodynamic indices improve during the educational training camp. The adaptation to physical activity begins with a 3-4 days of the educational training camp. It is advisable to regularly keep a diary of self-control, including both objective and subjective indicators of the functional state of football referees for the rational management of the training process. Drinking regime of the football referees require correction in the direction of increasing fluid intake. Football referees, who are older, tall and strong physique, require regular monitoring of the functional state of the organism and the individualization the training process in accordance with the peculiarities of adaptation to physical training.